Thai People’s Behavioral Trends in Auspicious Food Purchase: the Moderating Role of Astrological Superstitions - Shoedchin, Phrachun; Booranavitayaporn, Suphicha (Dusit Thani College Journal, 2024)
The objectives of this research are 1) to study behavioral trends in auspicious food purchase of different demographic factors, 2) to study the planned behavior theory factors that affect behavioral trends in auspicious food purchase, 3) to study marketing mix (7Ps) factors that affect behavioral trends in auspicious food purchase, 4) to study astrological superstition that affect the relationship between the theory of planned behavior factors and behavioral trends in auspicious food purchase, and 5) to study astrological superstition that affects the relationship between marketing mix (7Ps) factors and behavioral trends in auspicious food purchase. Using the quota sampling technique, the samples were selected by considering the proportion of the population in Thailand. The online data collection method involved creating a questionnaire in Google Form and sending the link to various groups in 6 regions for a total of 400 respondents. The statistics used in this study included descriptive statistics, F-test (ANOVA), multiple regression, and moderation analysis. Results of The study were 1) Thai population who are government officers have different behavior trends in auspicious food purchase level, 2) attitude towards behavior, and perceived ability to control behavior factors positively affect the behavior trends in auspicious food purchase level, 3) product, place, and physical evidence factors positively affect the behavior trends in auspicious food purchase level, 4) astrological superstition factor, as the moderator, affects the relationship of theory of planned behavior factors and the behavior trends in auspicious food purchase level, and 5) astrological superstition factor, as the moderator, has no effect on the relationship of marketing mix factors and the behavior trends in auspicious food purchase.